Relación entre el gasto público en promoción turismo y el desarrollo del sector turismo en la región Loreto 2014–2023 - Armas Crisostomo, Juan Jose (2025)
This research analyzes the relationship between public spending on tourism promotion and the development of the tourism sector in the Loreto region during the period 2014–2023. Using a quantitative approach, secondary data were collected from official sources such as the MEF, MINCETUR, and INEI. Descriptive and correlational statistical methods were applied, particularly the Spearman coefficient, to assess the association between key variables such as allocated budget, investment in tourism infrastructure, tourist flow, and average length of stay in lodging establishments. The results revealed a positive and significant correlation between public expenditure and the behavior of the tourism sector, especially in attracting domestic tourists and increasing the average length of stay. However, the relationship was stronger in some components, such as infrastructure, and more moderate in others, highlighting the need for more strategic planning of public investment. It is concluded that although tourism has gained greater budgetary relevance in recent years, its impact still largely depends on the efficiency, targeting, and sustainability of public investment. This study provides valuable evidence for the design of public policies aimed at promoting regional tourism development.